Representations Around Maternity: From Praise to Social Critics (Research, Society and Development, 2019)
The social networks help to circulate themes related to the social roles that women play and that contribute to the formation of the construction of an identity of the feminine. The objective of this study is to investigate how the problem of the construction of the feminine materializes discursively and rhetorically. More specifically, such as praise and criticism about motherhood, social networks (blogs) praise or criticize the issue in question. The analysis of the amplifying arguments, categorized in the form of discourses reported, and their discursive manifestations in the enunciative heterogeneities (direct, indirect, indirect free speech) were analyzed. From the analysis, it was possible to conclude that through praise, criticism has been implanted in these discourses, revealing socially shared beliefs and values while militant forces on the social role of women have been raised.